Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1186/1476-0711-12-3
|View full text |Cite
|
Sign up to set email alerts
|

Primary antibiotic resistance and associated mechanisms in Helicobacter pylori isolates from Senegalese patients

Abstract: BackgroundAntibiotic combination therapy for Helicobacter pylori eradication must be adapted to local resistance patterns, but the epidemiology of H. pylori resistance to antibiotics is poorly documented in Africa. The aim was to determine the antibiotic resistance rates, as well as the associated molecular mechanisms, of strains isolated in Dakar, Senegal.MethodsOne hundred and eight H. pylori strains were isolated between 2007 and 2009 from 108 patients presenting with upper abdominal pain to the Gastroenter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 20 publications
6
44
2
Order By: Relevance
“…In one study, clarithromycin resistance was reported in 47.5% of patients with dyspepsia in Turkey [41] . In sharp contrast to other Asian countries, no resistance to clarithromycin has been reported in Malaysia [42] and the prevalence of resistance to clarithromycin in Gambia and Senegal also remains very low [43,44] . Resistance to clarithromycin has also risen by > 20% in Southern Europe, although in Northern Europe the resistance rate is less than 10% [45] compared to 1.5% in a random adult Swedish population [46] and 7.5% in central Germany [47] .…”
Section: Current Antibiotic Resistance In Worldwidementioning
confidence: 90%
See 2 more Smart Citations
“…In one study, clarithromycin resistance was reported in 47.5% of patients with dyspepsia in Turkey [41] . In sharp contrast to other Asian countries, no resistance to clarithromycin has been reported in Malaysia [42] and the prevalence of resistance to clarithromycin in Gambia and Senegal also remains very low [43,44] . Resistance to clarithromycin has also risen by > 20% in Southern Europe, although in Northern Europe the resistance rate is less than 10% [45] compared to 1.5% in a random adult Swedish population [46] and 7.5% in central Germany [47] .…”
Section: Current Antibiotic Resistance In Worldwidementioning
confidence: 90%
“…In Vietnam, the resistance rate was 69.9% among 103 strains [40] . Unlike the clarithromycin resistance rate, there was a high prevalence of resistance to metronidazole (75.5%) in Malaysia [42] , a 76.8% rate in Iran [54] and a high resistance rate in Africa [43,44] . Another study showed that 80% of strains in Mexico were resistant to metronidazole [55] .…”
Section: Current Antibiotic Resistance In Worldwidementioning
confidence: 97%
See 1 more Smart Citation
“…Matsuzaki et al found amino acid 87 and 91 sites were located in the N-terminal region of GyrA protein combined with DNA. Seck et al also found no gyrA mutation in some LVX-resistant strains, 34 suggesting other resistance-related mechanisms such as efflux pump, 35 membrane permeability, autophagy, globular transformation, and even new resistant genes. 31,32 Some studies showed that sitafloxacin and garenoxacin may overcome the antibiotic resistance of H. pylori with gyrA mutation.…”
Section: Discussionmentioning
confidence: 99%
“…However, while the dissemination and high prevalence of antibiotic resistance in Gram-negative bacilli has been described worldwide and could be associated with international travel and tourism 5, few studies have described the prevalence and mechanism of antibiotic resistance in Enterobacteriaceae from northern Africa, especially Senegal 3. Indeed, the few studies conducted in this region were on Enterobacteriaceae species including Shigella flexneri and Salmonella enterica , which are not classified as dominant nosocomial pathogens 6,7. In this region, we have recently described the emergence of clinical multidrug-resistant Gram-negative bacteria, especially Acinetobacter baumannii , resistant to all β-lactams including the carbapenems 8, which has never been reported before in Senegal.…”
Section: Introductionmentioning
confidence: 99%